Comparison of Database Management Systems. A comparison of common Database Management Systems - Arneson, Simon; Berntsson, Joakim; Larsson, Victor; Takman, Simon Larsson; Nordmark, Erik; Talebi, Pedram (My University, 2016)
Data can be referred to as objects or events stored on digital media. The evolution of IT solutions has sprung an interest in developing systems to store this type of data more efficiently. The modern method of storing general data is by utilizing a database, which is an organized collection of logically related data. Different types of databases suit various needs, therefore the purpose of this project is to compare the leading database solutions with each other. The databases chosen for this project are: MySQL, Neo4j and MongoDB. Furthermore we collaborate with two companies in order to acquire hands-on information of how companies work with data. This is done by developing modules for their web applications. The insight and data obtained through these companies is used to create test cases which is then benchmarked on the different database management systems. The test results indicates that MongoDB has overall the best performance. However, during a few complex test cases MongoDB lacks in performance. Neo4j performs worse on more test cases than MongoDB, and MySQL is by far the most consistent of these three technologies. The outcome is similar to our expectations and confirms parts of the related work that has been researched.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science